Cholecystectomy of choice for one skin incision between 5 and B cm: Our experience: Regarding 28 consecutive cases - Estefan, Alberto; Iacopino, Julio; Dutto, Gabriel; Bruno, Gerardo; Ramos, Edgardo; Praderi, Raúl (Cirugía del Uruguay, 1994)
A series of 28 consecutive and non-selected elective cholecystectomies were carried out through a 5 to 8 cm cutaneous incision. No unsurmountable technical difficulties were observed. The incision was only widened in two circumstances: a) wrong site and b) associated asymptomatic choledochal lithiasis. Transcystic per-operative cholangiography was performed in al/ cases. A previous echography far determination of the exact topography of the ga/1-bladder and the hepatic pedicle is considered fundamental. There were no post-operative complications.